FEMINIST APPROACHES TO LINGUISTIC STUDIES - Karimova Madinakhon; Saida Gaziyeva Turgunovna (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Feminist approaches to linguistic studies are examined in this paper with an eye on the junction of language and gender. It looks at how language both reflects and reinforces power relations and social conventions as well as the ways in which feminist thinkers question conventional language structures. Through a feminist perspective, the paper examines many linguistic approaches in order to address problems like gendered language usage, the depiction of women in discourse, and the effects of language on identity and emancipation. In the end, it promotes a more inclusive and critical view of language that acknowledges the part gender plays in forming society institutions and communication.